Dynamic filtration in baleen whales: recent discoveries and emerging trends - Werth, Alexander J.; Potvin, Jean (Frontiers in Marine Science, 2024)
Recent findings have greatly improved our understanding of mysticete oral filtration, and have upended the traditional view of baleen filtration as a simple process. Flow tank experiments, telemetric tag deployment on whales, and other lab and field methods continue to yield new data and ideas. These suggest that several mechanisms arose from ecological, morphological, and biomechanical adaptations facilitating the evolution of extreme body size in Mysticeti. Multiple lines of evidence strongly support a characterization of baleen filtration as a conceptually dynamic process, varying according to diverse intraoral locations and times of the filtration process, and to other prevailing conditions. We review and highlight these lines of evidence as follows. First, baleen appears to work as a complex metafilter comprising multiple components with differing properties. These include major and minor plates and eroded fringes (AKA bristles or hairs), as well as whole baleen racks. Second, it is clear that different whale species rely on varied ecological filtration modes ranging from slow skimming to high-speed lunging, with other possibilities in between. Third, baleen filtration appears to be a highly dynamic and flow-dependent process, with baleen porosity not only varying across sites within a single rack, but also by flow direction, speed, and volume. Fourth, findings indicate that baleen (particularly of balaenid whales and possibly other species) generally functions not as a simple throughput sieve, but instead likely uses cross-flow or other tangential filtration, as in many biological systems. Fifth, evidence reveals that the time course of baleen filtration, including rate of filter filling and clearing, appears to be more complex than formerly envisioned. Flow direction, and possibly plate and fringe orientation, appears to change during different stages of ram filtration and water expulsion. Sixth, baleen’s flexibility and related biomechanical properties varies by location within the whole filter (=rack), leading to varying filtration conditions and outcomes. Seventh, the means of clearing/cleaning the baleen filter, whether by hydraulic, hydrodynamic, or mechanical methods, appears to vary by species and feeding type, notably intermittent lunging versus continuous skimming. Together, these and other findings of the past two decades have greatly elucidated processes of baleen filtration, and heightened the need for further research. Many aspects of baleen filtration may pertain to other biological filters; designers can apply several aspects to artificial filtration, both to better understand natural systems and to design and manufacture more effective synthetic filters. Understanding common versus unique features of varied filtration phenomena, both biological and artificial, will continue to aid scientific and technical understanding, enable fruitful interdisciplinary partnerships, and yield new filter designs.